TURRA-KALANGI: TRADITIONAL COMMUNICATION OF NIMAR REGION OF MADHYA PRADESH: तुर्रा-कलंगी: मध्यप्रदेष के निमाड़ क्षेत्र का परम्परागत संचार - Sharma, Anuradha (International Journal of Research -GRANTHAALAYAH, 2019)
In the Nimar region of Madhya Pradesh, the stage or theater activities like Hindi provinces are currently less. Where other provinces of India have theater identity and awareness in their respective languages, there is neither identity nor awareness in Hindi provinces. It seems that there is a continuous cultural decline in Hindi states. For this, terrible economic decline, unemployment and corruption as well as anomalous social conditions are responsible. Apart from this, excessive publicity of internet along with radio and television is also responsible. मध्यप्रदेष के निमाड़ क्षेत्र में हिन्दी प्रांतों की तरह मंच अथवा रंगमंच की गतिविधियां वर्तमान में कम ही है। जहां भारत के अन्य प्रांतों में अपनी-अपनी भाषा में रंगमंच की पहचान एवं जागरूकता विद्यमान है वहां हिन्दी प्रांतों में न पहचान है न जागरूकता। ऐसा प्रतीत होता है कि हिन्दी प्रदेषों में लगातार सांस्कृतिक हृास हो रहा है। इसके लिये भयानक आर्थिक गिरावट, बेरोजगारी और भ्रष्टाचार के साथ-साथ विषम सामाजिक स्थितियां जिम्मेदार है। इसके अलावा रेडियो और टेलीविजन के साथ इन्टरनेट का अत्यधिक प्रचार भी जिम्मेदार है।